Literacy Character Education Planning to Strengthen the Pancasila Student Profile through Local Culture in Early Childhood Education - Suratmi, Suratmi; Hartono, Hartono; Diana (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study explores the planning of character education projects to strengthen the Pancasila student profile through local culture in early childhood education at TK Sukoharjo 1 and TK Desa Majasto 02. Employing a descriptive qualitative case study approach, data were gathered through interviews, observations, and document studies. The findings reveal comprehensive strategies for planning, implementing, and evaluating character education projects. At TK Sukoharjo 01, the project involved forming a facilitator team, identifying readiness stages, and developing specific learning modules. Implementation utilized real-life experiences such as gardening and local markets, while evaluation focused on cooperation, communication, and care. At TK Desa Majasto 02, the project preparation included curriculum development, facilitator team formation, and methods centered around the local culture of